المؤشرات الاقتصادية للعمل السياحي ودورها في التنمية المستدامة في الجزائر - اسماعيل, مراد; ملاحي, رقية (جامعة الوادي - University of Eloued, 2017)
تعتبر صناعة السياحة في الوقت الحالي عامل مهم للنمو الاقتصادي بالنسبة للدول التي تتصف بحركة سياحية فعالة، ذلك لأن السياحة تساهم في زيادة الدخل القومي وتحسين رصيد ميزان المدفوعات، وأصبحت السياحة ليست ترفيه فقط وإنما صناعة وطنية يتم استغلالها واستثمارها لغرض صالح البلد والمواطنين، وبالتالي القطاع السياحي يساهم في تحقيق التنمية الاقتصادية . وبناء على ما سبق تتمثل إشكالية هذا البحث في: ما مدى مساهمة القطاع السياحي في تحقيق التنمية الاقتصادية الجزائر ؟ من هذا المنطلق اشتملت منهجية الدراسة على العناصر التالية: ـ المنهج الوصفي والتحليلي؛ منهج دراسة حالة؛ المنهج الاستنباطي. من خلال إبراز واقع الصناعة السياحية و التنمية المستدامة و آفاق المؤشرات الاقتصادية للسياحة في الجزائر لسنة 2026،ومن تم دراسة حالة السوق السياحي في الفترة المتزامنة من 2010/ 2017 The tourism industry is currently an important factor for economic growth for countries with an effective tourist traffic. Tourism contributes to increasing national income and improving the balance of payments balance. Tourism is not only entertainment but a national industry exploited and exploited for the benefit of the country and its citizens. Contributes to economic development. Based on the above, the problem of this research is: What is the contribution of the tourism sector to economic development Algeria? From this point of view, the methodology of the study included the following elements: descriptive and analytical approach; case study methodology; By highlighting the reality of tourism industry and sustainable development and the prospects of economic indicators of tourism in Algeria for the year 2026, and the study of the situation of the tourism market in the concurrent period of 2010 / 2017.
Economic indicators of tourism work and its role in sustainable development in Algeria.
مقال
Keywords: tourism, employment, exports, GDP, sustainable development.